Analysis of Food Consumption in Hungary - Katalin Tari; József Lehota; Nándor Komáromi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The background of our research considers consumers' awareness about the contents of their food and investigates the labels and wording on food packaging. The 'organic' labels on this packaging hold different levels of importance for Hungarian people based on their age and social-economic status. This topic will remain highly relevant, since most companies desire to understand the behaviour of their Hungarian consumers. By examining consumers' behaviour patterns and inexpensive marketing tips, companies can consider the most effective method to increase the purchase of their products. As such, consumer behaviour patterns should be researched in the short term based on the use of specific products or on the use of generic brands versus personal preferences. Currently, the roles of healthawareness and cost-consciousness are changing, as are environmental protection regulations and consumers' awareness of the dangers of hazardous substances. The article focuses on the analysis of Hungarian behaviour patterns related to foodstuff grocery consumption. The database was taken from IPSOS Ltd. (N=1038 people), but 883 people were selected from the initial sample, based on inclusive criteria (aged between 18 and 70), while people with extreme incomes were excluded (as outliers).
Keywords: 330; food marketing; Hungarian customer; costumer behaviour; packaging; label; social-classes